Effect of Ecoenzyme Addition on Corn-Based Trichoderma asperellum Formula on Spore Count - Tarigan, Siti Nadiah Zahra Br; Anhar, Azwir; Farma, Sisca Alicia; Violita, Violita (Jurnal Biologi Tropis, 2025)
Trichoderma asperellum is recognized as an effective biocontrol agent and plant growth promoter, playing a vital role in sustainable agriculture. To enhance the efficacy of Trichoderma formulations, ecoenzyme supplementation has been proposed as a promising approach. This study investigated the effect of ecoenzyme supplementation on the spore count of corn-based Trichoderma asperellum formulations. A Completely Randomized Design (CRD) was employed with five treatments and five replicates, and spore counts were assessed under varying concentrations of ecoenzyme (0%, 20%, 40%, 60%, and 80%). The results indicated that a 60% ecoenzyme concentration significantly increased the spore count, reaching a maximum of 252.32 × 10⁶ spores. However, higher concentrations (80%) resulted in a decreased spore count (174.88 × 10⁶), which was similar to that of the control (172.6 × 10⁶), likely due to toxic effects or nutrient imbalances. These findings highlight the importance of selecting the optimal ecoenzyme concentration to maximize the spore count of Trichoderma asperellum, thereby contributing to more effective biocontrol and biofertilizer applications in sustainable agricultural practices.